Locating Digital Humanities: Teaching e-Literature in the Pacific - Sarce, John Paolo (Archīum Ateneo, 2019)
Teaching e-literature (electronic literature) is an academic space for both explorations and contestations in the East. However, the East is not a monolithic location or space; the East that lies near and within the Pacific is still divided, based on the countries’ locations and economic statuses. The Philippines, as a country located specifically in the Southeast of the Pacific, is still experiencing several struggles over teaching and creating e-literature, a part of the ‘Digital Humanities’ that cultivate and nourish, while at the same time deconstructing different forms of art. Teaching in the twenty-first century is already a huge challenge for every pedagogue; thus, to teach e-literature is another challenge that both educators and school administrators have to work on and excel at when they prepare their students for the future. Not only ‘teaching’ and ‘e-literature’ or Digital Humanities (in the broader sense) are sites that should be considered and interrogated critically under different researches focusing on these new trends in academia, but also ‘location’ should be taken into consideration within this field. This essay interrogates and presents the complications of teaching e-literature, once it is juxtaposed to ‘location’. Studying location vis-à-vis teaching and e-literature creates tension and nuances that, once critically interrogated and examined, appear since location can either denote resistance or acceptance when analysed through the lenses of post-colonial theory. This chapter presents the multileveled and varied reaction of a Southeast Pacific country towards Digital Humanities, due to their former colonialisation and to their social and economic statuses that, in spite of technology’s invasions across the world e-literature or Digital Humanities, are still outside or weak on the Philippines’ academic radar. Our perception of e-literature is currently affected by such forces as cultural and economic ones, which makes teaching e-literature almost impossible. But because of the current changes in education in the Philippines, our perception on e-literature is now possibly able to change. Teaching e-literature in our classrooms now can open up a space of mutual understanding and for bridging the widening gaps between science, technology, and the humanities.